2015
DOI: 10.1017/s0022377815000823
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagrams of forced magnetic reconnection in Taylor’s model

Abstract: Recent progress in the understanding of how externally driven magnetic reconnection evolves is organized in terms of parameter space diagrams. These diagrams are constructed using four pivotal dimensionless parameters: the Lundquist number S, the magnetic Prandtl number P m , the amplitude of the boundary perturbationΨ 0 , and the perturbation wave numberk. This new representation highlights the parameter regions of a given system in which the magnetic reconnection process is expected to be distinguished by a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…That is, reconnection sets in slowly, and, when it does, it is a slow reconnection. Alternative reconnection scenarios for the Taylor-Hahm-Kulsrud problem are reviewed in [37]. It is found that fast reconnection occurs if the boundary perturbation amplitude is large enough that the current sheet breaks up into plasmoids, due to an instability discussed in §4f.…”
Section: (A) Formation Of Current Singularitiesmentioning
confidence: 99%
“…That is, reconnection sets in slowly, and, when it does, it is a slow reconnection. Alternative reconnection scenarios for the Taylor-Hahm-Kulsrud problem are reviewed in [37]. It is found that fast reconnection occurs if the boundary perturbation amplitude is large enough that the current sheet breaks up into plasmoids, due to an instability discussed in §4f.…”
Section: (A) Formation Of Current Singularitiesmentioning
confidence: 99%
“…i.e., the critical Lundquist number for the stability of the sheet increases with increasing plasma viscosity due to the reduction of the outflow velocity [31,62]. In particular, in the limit P m ≪ 1 we get S c ≈ ǫ −2 c [7, 10], whereas in the limit P m ≫ 1 it follows that S c ≈ ǫ −2 c P 1/2 m , which agrees with the condition proposed by Loureiro et al [17].…”
Section: Fastest Growing Modementioning
confidence: 99%
“…(2013), Comisso et al. (2015 a , b ). Low-order resonant structures within the plasma that are excited, Boozer & Pomphrey (2010), White (2013) by geometric change resist the formation of magnetic islands by developing shielding current sheets. A long diffusion (possibly anomalous) time scale on which plasma and magnetic flux leak and mix between subregions through weak spots in the current sheets , violating the mass and flux isolation of the subregions assumed in MRxMHD and also violating entropy conservation.…”
Section: Plasma Relaxationmentioning
confidence: 99%
“…(2013), Comisso et al. (2015 a , b ). Low-order resonant structures within the plasma that are excited, Boozer & Pomphrey (2010), White (2013) by geometric change resist the formation of magnetic islands by developing shielding current sheets.…”
Section: Plasma Relaxationmentioning
confidence: 99%
See 1 more Smart Citation